Effects of canagliflozin on initiation of insulin and other antihyperglycaemic agents in the CANVAS Program. Issue 11 (24th August 2020) - Matthews, David R.; Wysham, Carol; Davies, Melanie; Slee, April; Alba, Maria; Lee, Mary; Perkovic, Vlado; Mahaffey, Kenneth W.; Neal, Bruce
Abstract: This study compared initiation of insulin and other antihyperglycaemic agents (AHAs) with canagliflozin versus placebo for participants with type 2 diabetes and a history/high risk of cardiovascular disease in the CANagliflozin cardioVascular Assessment Study (CANVAS) Program. After 1 year, fewer participants treated with canagliflozin versus placebo initiated any AHA (7% vs. 16%), insulin (3% vs. 9%) or any non‐insulin AHA (5% vs. 12%) ( P < .001 for all); overall AHA initiation rates increased over time but were consistently lower with canagliflozin compared with placebo. During the study, the likelihood of initiating insulin was 2.7 times lower for participants treated with canagliflozin compared with placebo (hazard ratio, 0.37; 95% CI: 0.31, 0.43; P < .001). The time difference between 10% of patients in the canagliflozin and placebo groups being initiated on insulin from the beginning of the trial was about 2 years. Time to initiation of other AHAs, including metformin, dipeptidyl peptidase‐4 inhibitors, glucagon‐like peptide‐1 receptor agonists and sulphonylureas, was also delayed for canagliflozin versus placebo ( P < .001 for each). Compared with placebo, canagliflozin delayed the need for initiation of other AHAs and delayed time to insulin therapy, an outcome that is important to many people with diabetes.